L’Altérité, une notion vraiment sans histoire ? Eclairage philosophique sur une notion devenue incontournable en éducation - Muriel Briançon; Jeanne Mallet; Chantal Eymard (Recherches en Éducation)
This theoretical article reviews the history of philosophy in search of a definition of the notion of alterity. This notion is helpful for understanding the learning process in the fields of education and training. We argue however, that the term is employed excessively, often without an understanding of its significance and especially with a disregard for its historical roots. The etymology of the word is Greek and refers to the accidental Platonician discovery of “otherness” as difference (έτερότης). Yet the widespread use of this term cannot be understood without taking into account the parallel and stifled history of the concept of non-being (μή έόν). Alterity could consequently be understood as a substitute or overriding notion which identity has been forgotten. Because education researchers have everything to gain from recognizing its historical and philosophical roots, we propose a relevant and precise review of the notion: its three dimensions, its transgressive and emancipatory features and its capacity for teaching.